Reattachment of Fractured Tooth-Series of 2 Case Reports - Satabdi Pattanaik1, Shashirekha G.2, Sumit Dash3, Rini Behera1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Most common consequences of trauma is the crown fracture, mainly maxillary anterior tooth due to itsforward positioning in the arch. Understanding the outcome of the planned treatment gives an idea regardingthe prognosis of that particular treatment. Various options are available for the treatment of fractured tooth.Among all reattachment of fractured coronal segment to that tooth provides instant esthetic, as it restoresthe original form, colour, contour, surface texture and also gives a psychological comfort to the patient. Thisclinical case report focuses on the successful reattachment of two fractured coronal crowns using glass-fibrereinforced composite post. Since, both of the fractured teeth were of complex type, endodontic treatmentwas performed for both of the cases. At the end, a natural-looking restoration is achieved.